Intravenous Immunoglobulin as an Immunomodulating Agent in Antineutrophil Cytoplasmic Antibody–Associated Vasculitides: A French Nationwide Study of Ninety‐Two Patients. Issue 3 (March 2016) - Crickx, Etienne; Machelart, Irène; Lazaro, Estibaliz; Kahn, Jean‐Emmanuel; Cohen‐Aubart, Fleur; Martin, Thierry; Mania, Alexandre; Hatron, Pierre‐Yves; Hayem, Gilles; Blanchard‐Delaunay, Claire; de Moreuil, Claire; Le Guenno, Guillaume; et al.
Abstract : Objective: Intravenous immunoglobulin (IVIG) represents a therapeutic alternative in antineutrophil cytoplasmic antibody–associated vasculitides (AAV), but its efficacy has been evaluated in only 2 small prospective trials. The aim of this study was to evaluate the efficacy and safety of IVIG in patients with AAV. Methods: We conducted a nationwide retrospective study of patients who received IVIG as immunomodulatory therapy for AAV. Results: A total of 92 patients (mean age 51 years) presenting with either granulomatosis with polyangiitis (Wegener's) (68%), eosinophilic granulomatosis with polyangiitis (Churg‐Strauss) (22%), or microscopic polyangiitis (10%) received at least 1 course of IVIG. Antineutrophil cytoplasmic antibodies were present in 72% during the flare that required IVIG, as determined by immunofluorescence assay. IVIG was initiated because of relapsing disease in 83% of cases. IVIG was given for a median of 6 months (range 1–156 months) and in combination with corticosteroids in 21% of the patients or with other immunosuppressive agents in 77%. Efficacy of IVIG was assessed in the entire population and in a subset of 34 patients with unmodified background therapy. Remission rates at 6 months were 56% in the entire population and 58% in the unmodified background therapy group. Refractory disease and treatment failure at 6 months were observed in 7% and 18% in the whole population and 3% and 21% in the unmodified background therapy group, respectively. Adverse events (AEs) occurred in 33%, including serious AEs in 12% and AEs leading to discontinuation of IVIG in 7%. Conclusion: This large study shows the clinical benefit of IVIG as adjunctive therapy, with an acceptable tolerance profile, and thus supports its use in AAV patients with refractory or relapsing disease.